Analysis of Macro Nutritional Substances, Branched-Chain Amino Acids, Viscosity Enteral Formula for Hepatic Cirrhosis Patients - Puspita, Eggi; Siregar, Afriyana; Yuniarti, Hana (jitek, 2022)
Patients with hepatic impairment are particularly at risk of malnutrition because of impaired absorption, hypermetabolism, and poor oral intake. Enteral diet therapy based on pumpkin and soybean flour is one of the local foods functional as an alternative enteral formula for patients with liver cirrhosis because it contains high Branched-Chain Amino Acids (BCAA) and Medium-Chain Triglyceride (MCT). The purpose of this study was to analyze the nutritional value (proximate test), BCAA test (Leucine, Isoleucine, Valine) and Viscosity Test (thickness) and organoleptic test of enteral formulas of patients with liver cirrhosis from pumpkin and soybean flour. This descriptive qualitative research method uses three levels of treatment, comparison of pumpkin with soybean powder. The characteristics analyzed are macronutrients (energy, protein, fat, carbohydrates), BCAA (leucine, isoleucine, valine), viscosity. Statistical analysis with One Way Anova and organoleptic test with a hedonic method. The macronutrient content analysis following the diet's requirements and principles was enteral formula two at a relative concentration (80:20). The statistical test results showed a p-value of 0.000 (<0.05), which means a significant difference in the content of leucine, isoleucine, and valine in the three enteral formulas. Increasing the ratio of pumpkin tends to increase the viscosity of the enteral cirrhosis formula. The enteral formula has characteristics per 1000 ml as follows: 38 grams of protein, 161.1 grams of carbohydrates, 25.2 grams of fat, 1023 kcal of energy, 5743.43 mg of BCAAs, and the results of the organoleptic test selected for the enteral formula 2.